### (0) Obligation:

Runtime Complexity TRS:
The TRS R consists of the following rules:

if(true, x, y) → x
if(false, x, y) → y
eq(0, 0) → true
eq(0, s(x)) → false
eq(s(x), 0) → false
eq(s(x), s(y)) → eq(x, y)
app(nil, l) → l
app(cons(x, l1), l2) → cons(x, app(l1, l2))
app(app(l1, l2), l3) → app(l1, app(l2, l3))
mem(x, nil) → false
mem(x, cons(y, l)) → ifmem(eq(x, y), x, l)
ifmem(true, x, l) → true
ifmem(false, x, l) → mem(x, l)
inter(x, nil) → nil
inter(nil, x) → nil
inter(app(l1, l2), l3) → app(inter(l1, l3), inter(l2, l3))
inter(l1, app(l2, l3)) → app(inter(l1, l2), inter(l1, l3))
inter(cons(x, l1), l2) → ifinter(mem(x, l2), x, l1, l2)
inter(l1, cons(x, l2)) → ifinter(mem(x, l1), x, l2, l1)
ifinter(true, x, l1, l2) → cons(x, inter(l1, l2))
ifinter(false, x, l1, l2) → inter(l1, l2)

Rewrite Strategy: FULL

### (1) DecreasingLoopProof (EQUIVALENT transformation)

The following loop(s) give(s) rise to the lower bound Ω(n1):
The rewrite sequence
eq(s(x), s(y)) →+ eq(x, y)
gives rise to a decreasing loop by considering the right hand sides subterm at position [].
The pumping substitution is [x / s(x), y / s(y)].
The result substitution is [ ].

### (3) RenamingProof (EQUIVALENT transformation)

Renamed function symbols to avoid clashes with predefined symbol.

### (4) Obligation:

Runtime Complexity Relative TRS:
The TRS R consists of the following rules:

if(true, x, y) → x
if(false, x, y) → y
eq(0', 0') → true
eq(0', s(x)) → false
eq(s(x), 0') → false
eq(s(x), s(y)) → eq(x, y)
app(nil, l) → l
app(cons(x, l1), l2) → cons(x, app(l1, l2))
app(app(l1, l2), l3) → app(l1, app(l2, l3))
mem(x, nil) → false
mem(x, cons(y, l)) → ifmem(eq(x, y), x, l)
ifmem(true, x, l) → true
ifmem(false, x, l) → mem(x, l)
inter(x, nil) → nil
inter(nil, x) → nil
inter(app(l1, l2), l3) → app(inter(l1, l3), inter(l2, l3))
inter(l1, app(l2, l3)) → app(inter(l1, l2), inter(l1, l3))
inter(cons(x, l1), l2) → ifinter(mem(x, l2), x, l1, l2)
inter(l1, cons(x, l2)) → ifinter(mem(x, l1), x, l2, l1)
ifinter(true, x, l1, l2) → cons(x, inter(l1, l2))
ifinter(false, x, l1, l2) → inter(l1, l2)

S is empty.
Rewrite Strategy: FULL

Infered types.

### (6) Obligation:

TRS:
Rules:
if(true, x, y) → x
if(false, x, y) → y
eq(0', 0') → true
eq(0', s(x)) → false
eq(s(x), 0') → false
eq(s(x), s(y)) → eq(x, y)
app(nil, l) → l
app(cons(x, l1), l2) → cons(x, app(l1, l2))
app(app(l1, l2), l3) → app(l1, app(l2, l3))
mem(x, nil) → false
mem(x, cons(y, l)) → ifmem(eq(x, y), x, l)
ifmem(true, x, l) → true
ifmem(false, x, l) → mem(x, l)
inter(x, nil) → nil
inter(nil, x) → nil
inter(app(l1, l2), l3) → app(inter(l1, l3), inter(l2, l3))
inter(l1, app(l2, l3)) → app(inter(l1, l2), inter(l1, l3))
inter(cons(x, l1), l2) → ifinter(mem(x, l2), x, l1, l2)
inter(l1, cons(x, l2)) → ifinter(mem(x, l1), x, l2, l1)
ifinter(true, x, l1, l2) → cons(x, inter(l1, l2))
ifinter(false, x, l1, l2) → inter(l1, l2)

Types:
if :: true:false → if → if → if
true :: true:false
false :: true:false
eq :: 0':s → 0':s → true:false
0' :: 0':s
s :: 0':s → 0':s
app :: nil:cons → nil:cons → nil:cons
nil :: nil:cons
cons :: 0':s → nil:cons → nil:cons
mem :: 0':s → nil:cons → true:false
ifmem :: true:false → 0':s → nil:cons → true:false
inter :: nil:cons → nil:cons → nil:cons
ifinter :: true:false → 0':s → nil:cons → nil:cons → nil:cons
hole_if1_0 :: if
hole_true:false2_0 :: true:false
hole_0':s3_0 :: 0':s
hole_nil:cons4_0 :: nil:cons
gen_0':s5_0 :: Nat → 0':s
gen_nil:cons6_0 :: Nat → nil:cons

### (7) OrderProof (LOWER BOUND(ID) transformation)

Heuristically decided to analyse the following defined symbols:
eq, app, mem, inter

They will be analysed ascendingly in the following order:
eq < mem
app < inter
mem < inter

### (8) Obligation:

TRS:
Rules:
if(true, x, y) → x
if(false, x, y) → y
eq(0', 0') → true
eq(0', s(x)) → false
eq(s(x), 0') → false
eq(s(x), s(y)) → eq(x, y)
app(nil, l) → l
app(cons(x, l1), l2) → cons(x, app(l1, l2))
app(app(l1, l2), l3) → app(l1, app(l2, l3))
mem(x, nil) → false
mem(x, cons(y, l)) → ifmem(eq(x, y), x, l)
ifmem(true, x, l) → true
ifmem(false, x, l) → mem(x, l)
inter(x, nil) → nil
inter(nil, x) → nil
inter(app(l1, l2), l3) → app(inter(l1, l3), inter(l2, l3))
inter(l1, app(l2, l3)) → app(inter(l1, l2), inter(l1, l3))
inter(cons(x, l1), l2) → ifinter(mem(x, l2), x, l1, l2)
inter(l1, cons(x, l2)) → ifinter(mem(x, l1), x, l2, l1)
ifinter(true, x, l1, l2) → cons(x, inter(l1, l2))
ifinter(false, x, l1, l2) → inter(l1, l2)

Types:
if :: true:false → if → if → if
true :: true:false
false :: true:false
eq :: 0':s → 0':s → true:false
0' :: 0':s
s :: 0':s → 0':s
app :: nil:cons → nil:cons → nil:cons
nil :: nil:cons
cons :: 0':s → nil:cons → nil:cons
mem :: 0':s → nil:cons → true:false
ifmem :: true:false → 0':s → nil:cons → true:false
inter :: nil:cons → nil:cons → nil:cons
ifinter :: true:false → 0':s → nil:cons → nil:cons → nil:cons
hole_if1_0 :: if
hole_true:false2_0 :: true:false
hole_0':s3_0 :: 0':s
hole_nil:cons4_0 :: nil:cons
gen_0':s5_0 :: Nat → 0':s
gen_nil:cons6_0 :: Nat → nil:cons

Generator Equations:
gen_0':s5_0(0) ⇔ 0'
gen_0':s5_0(+(x, 1)) ⇔ s(gen_0':s5_0(x))
gen_nil:cons6_0(0) ⇔ nil
gen_nil:cons6_0(+(x, 1)) ⇔ cons(0', gen_nil:cons6_0(x))

The following defined symbols remain to be analysed:
eq, app, mem, inter

They will be analysed ascendingly in the following order:
eq < mem
app < inter
mem < inter

### (9) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
eq(gen_0':s5_0(n8_0), gen_0':s5_0(n8_0)) → true, rt ∈ Ω(1 + n80)

Induction Base:
eq(gen_0':s5_0(0), gen_0':s5_0(0)) →RΩ(1)
true

Induction Step:
eq(gen_0':s5_0(+(n8_0, 1)), gen_0':s5_0(+(n8_0, 1))) →RΩ(1)
eq(gen_0':s5_0(n8_0), gen_0':s5_0(n8_0)) →IH
true

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

### (11) Obligation:

TRS:
Rules:
if(true, x, y) → x
if(false, x, y) → y
eq(0', 0') → true
eq(0', s(x)) → false
eq(s(x), 0') → false
eq(s(x), s(y)) → eq(x, y)
app(nil, l) → l
app(cons(x, l1), l2) → cons(x, app(l1, l2))
app(app(l1, l2), l3) → app(l1, app(l2, l3))
mem(x, nil) → false
mem(x, cons(y, l)) → ifmem(eq(x, y), x, l)
ifmem(true, x, l) → true
ifmem(false, x, l) → mem(x, l)
inter(x, nil) → nil
inter(nil, x) → nil
inter(app(l1, l2), l3) → app(inter(l1, l3), inter(l2, l3))
inter(l1, app(l2, l3)) → app(inter(l1, l2), inter(l1, l3))
inter(cons(x, l1), l2) → ifinter(mem(x, l2), x, l1, l2)
inter(l1, cons(x, l2)) → ifinter(mem(x, l1), x, l2, l1)
ifinter(true, x, l1, l2) → cons(x, inter(l1, l2))
ifinter(false, x, l1, l2) → inter(l1, l2)

Types:
if :: true:false → if → if → if
true :: true:false
false :: true:false
eq :: 0':s → 0':s → true:false
0' :: 0':s
s :: 0':s → 0':s
app :: nil:cons → nil:cons → nil:cons
nil :: nil:cons
cons :: 0':s → nil:cons → nil:cons
mem :: 0':s → nil:cons → true:false
ifmem :: true:false → 0':s → nil:cons → true:false
inter :: nil:cons → nil:cons → nil:cons
ifinter :: true:false → 0':s → nil:cons → nil:cons → nil:cons
hole_if1_0 :: if
hole_true:false2_0 :: true:false
hole_0':s3_0 :: 0':s
hole_nil:cons4_0 :: nil:cons
gen_0':s5_0 :: Nat → 0':s
gen_nil:cons6_0 :: Nat → nil:cons

Lemmas:
eq(gen_0':s5_0(n8_0), gen_0':s5_0(n8_0)) → true, rt ∈ Ω(1 + n80)

Generator Equations:
gen_0':s5_0(0) ⇔ 0'
gen_0':s5_0(+(x, 1)) ⇔ s(gen_0':s5_0(x))
gen_nil:cons6_0(0) ⇔ nil
gen_nil:cons6_0(+(x, 1)) ⇔ cons(0', gen_nil:cons6_0(x))

The following defined symbols remain to be analysed:
app, mem, inter

They will be analysed ascendingly in the following order:
app < inter
mem < inter

### (12) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
app(gen_nil:cons6_0(n583_0), gen_nil:cons6_0(b)) → gen_nil:cons6_0(+(n583_0, b)), rt ∈ Ω(1 + n5830)

Induction Base:
app(gen_nil:cons6_0(0), gen_nil:cons6_0(b)) →RΩ(1)
gen_nil:cons6_0(b)

Induction Step:
app(gen_nil:cons6_0(+(n583_0, 1)), gen_nil:cons6_0(b)) →RΩ(1)
cons(0', app(gen_nil:cons6_0(n583_0), gen_nil:cons6_0(b))) →IH
cons(0', gen_nil:cons6_0(+(b, c584_0)))

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

### (14) Obligation:

TRS:
Rules:
if(true, x, y) → x
if(false, x, y) → y
eq(0', 0') → true
eq(0', s(x)) → false
eq(s(x), 0') → false
eq(s(x), s(y)) → eq(x, y)
app(nil, l) → l
app(cons(x, l1), l2) → cons(x, app(l1, l2))
app(app(l1, l2), l3) → app(l1, app(l2, l3))
mem(x, nil) → false
mem(x, cons(y, l)) → ifmem(eq(x, y), x, l)
ifmem(true, x, l) → true
ifmem(false, x, l) → mem(x, l)
inter(x, nil) → nil
inter(nil, x) → nil
inter(app(l1, l2), l3) → app(inter(l1, l3), inter(l2, l3))
inter(l1, app(l2, l3)) → app(inter(l1, l2), inter(l1, l3))
inter(cons(x, l1), l2) → ifinter(mem(x, l2), x, l1, l2)
inter(l1, cons(x, l2)) → ifinter(mem(x, l1), x, l2, l1)
ifinter(true, x, l1, l2) → cons(x, inter(l1, l2))
ifinter(false, x, l1, l2) → inter(l1, l2)

Types:
if :: true:false → if → if → if
true :: true:false
false :: true:false
eq :: 0':s → 0':s → true:false
0' :: 0':s
s :: 0':s → 0':s
app :: nil:cons → nil:cons → nil:cons
nil :: nil:cons
cons :: 0':s → nil:cons → nil:cons
mem :: 0':s → nil:cons → true:false
ifmem :: true:false → 0':s → nil:cons → true:false
inter :: nil:cons → nil:cons → nil:cons
ifinter :: true:false → 0':s → nil:cons → nil:cons → nil:cons
hole_if1_0 :: if
hole_true:false2_0 :: true:false
hole_0':s3_0 :: 0':s
hole_nil:cons4_0 :: nil:cons
gen_0':s5_0 :: Nat → 0':s
gen_nil:cons6_0 :: Nat → nil:cons

Lemmas:
eq(gen_0':s5_0(n8_0), gen_0':s5_0(n8_0)) → true, rt ∈ Ω(1 + n80)
app(gen_nil:cons6_0(n583_0), gen_nil:cons6_0(b)) → gen_nil:cons6_0(+(n583_0, b)), rt ∈ Ω(1 + n5830)

Generator Equations:
gen_0':s5_0(0) ⇔ 0'
gen_0':s5_0(+(x, 1)) ⇔ s(gen_0':s5_0(x))
gen_nil:cons6_0(0) ⇔ nil
gen_nil:cons6_0(+(x, 1)) ⇔ cons(0', gen_nil:cons6_0(x))

The following defined symbols remain to be analysed:
mem, inter

They will be analysed ascendingly in the following order:
mem < inter

### (15) NoRewriteLemmaProof (LOWER BOUND(ID) transformation)

Could not prove a rewrite lemma for the defined symbol mem.

### (16) Obligation:

TRS:
Rules:
if(true, x, y) → x
if(false, x, y) → y
eq(0', 0') → true
eq(0', s(x)) → false
eq(s(x), 0') → false
eq(s(x), s(y)) → eq(x, y)
app(nil, l) → l
app(cons(x, l1), l2) → cons(x, app(l1, l2))
app(app(l1, l2), l3) → app(l1, app(l2, l3))
mem(x, nil) → false
mem(x, cons(y, l)) → ifmem(eq(x, y), x, l)
ifmem(true, x, l) → true
ifmem(false, x, l) → mem(x, l)
inter(x, nil) → nil
inter(nil, x) → nil
inter(app(l1, l2), l3) → app(inter(l1, l3), inter(l2, l3))
inter(l1, app(l2, l3)) → app(inter(l1, l2), inter(l1, l3))
inter(cons(x, l1), l2) → ifinter(mem(x, l2), x, l1, l2)
inter(l1, cons(x, l2)) → ifinter(mem(x, l1), x, l2, l1)
ifinter(true, x, l1, l2) → cons(x, inter(l1, l2))
ifinter(false, x, l1, l2) → inter(l1, l2)

Types:
if :: true:false → if → if → if
true :: true:false
false :: true:false
eq :: 0':s → 0':s → true:false
0' :: 0':s
s :: 0':s → 0':s
app :: nil:cons → nil:cons → nil:cons
nil :: nil:cons
cons :: 0':s → nil:cons → nil:cons
mem :: 0':s → nil:cons → true:false
ifmem :: true:false → 0':s → nil:cons → true:false
inter :: nil:cons → nil:cons → nil:cons
ifinter :: true:false → 0':s → nil:cons → nil:cons → nil:cons
hole_if1_0 :: if
hole_true:false2_0 :: true:false
hole_0':s3_0 :: 0':s
hole_nil:cons4_0 :: nil:cons
gen_0':s5_0 :: Nat → 0':s
gen_nil:cons6_0 :: Nat → nil:cons

Lemmas:
eq(gen_0':s5_0(n8_0), gen_0':s5_0(n8_0)) → true, rt ∈ Ω(1 + n80)
app(gen_nil:cons6_0(n583_0), gen_nil:cons6_0(b)) → gen_nil:cons6_0(+(n583_0, b)), rt ∈ Ω(1 + n5830)

Generator Equations:
gen_0':s5_0(0) ⇔ 0'
gen_0':s5_0(+(x, 1)) ⇔ s(gen_0':s5_0(x))
gen_nil:cons6_0(0) ⇔ nil
gen_nil:cons6_0(+(x, 1)) ⇔ cons(0', gen_nil:cons6_0(x))

The following defined symbols remain to be analysed:
inter

### (17) NoRewriteLemmaProof (LOWER BOUND(ID) transformation)

Could not prove a rewrite lemma for the defined symbol inter.

### (18) Obligation:

TRS:
Rules:
if(true, x, y) → x
if(false, x, y) → y
eq(0', 0') → true
eq(0', s(x)) → false
eq(s(x), 0') → false
eq(s(x), s(y)) → eq(x, y)
app(nil, l) → l
app(cons(x, l1), l2) → cons(x, app(l1, l2))
app(app(l1, l2), l3) → app(l1, app(l2, l3))
mem(x, nil) → false
mem(x, cons(y, l)) → ifmem(eq(x, y), x, l)
ifmem(true, x, l) → true
ifmem(false, x, l) → mem(x, l)
inter(x, nil) → nil
inter(nil, x) → nil
inter(app(l1, l2), l3) → app(inter(l1, l3), inter(l2, l3))
inter(l1, app(l2, l3)) → app(inter(l1, l2), inter(l1, l3))
inter(cons(x, l1), l2) → ifinter(mem(x, l2), x, l1, l2)
inter(l1, cons(x, l2)) → ifinter(mem(x, l1), x, l2, l1)
ifinter(true, x, l1, l2) → cons(x, inter(l1, l2))
ifinter(false, x, l1, l2) → inter(l1, l2)

Types:
if :: true:false → if → if → if
true :: true:false
false :: true:false
eq :: 0':s → 0':s → true:false
0' :: 0':s
s :: 0':s → 0':s
app :: nil:cons → nil:cons → nil:cons
nil :: nil:cons
cons :: 0':s → nil:cons → nil:cons
mem :: 0':s → nil:cons → true:false
ifmem :: true:false → 0':s → nil:cons → true:false
inter :: nil:cons → nil:cons → nil:cons
ifinter :: true:false → 0':s → nil:cons → nil:cons → nil:cons
hole_if1_0 :: if
hole_true:false2_0 :: true:false
hole_0':s3_0 :: 0':s
hole_nil:cons4_0 :: nil:cons
gen_0':s5_0 :: Nat → 0':s
gen_nil:cons6_0 :: Nat → nil:cons

Lemmas:
eq(gen_0':s5_0(n8_0), gen_0':s5_0(n8_0)) → true, rt ∈ Ω(1 + n80)
app(gen_nil:cons6_0(n583_0), gen_nil:cons6_0(b)) → gen_nil:cons6_0(+(n583_0, b)), rt ∈ Ω(1 + n5830)

Generator Equations:
gen_0':s5_0(0) ⇔ 0'
gen_0':s5_0(+(x, 1)) ⇔ s(gen_0':s5_0(x))
gen_nil:cons6_0(0) ⇔ nil
gen_nil:cons6_0(+(x, 1)) ⇔ cons(0', gen_nil:cons6_0(x))

No more defined symbols left to analyse.

### (19) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
eq(gen_0':s5_0(n8_0), gen_0':s5_0(n8_0)) → true, rt ∈ Ω(1 + n80)

### (21) Obligation:

TRS:
Rules:
if(true, x, y) → x
if(false, x, y) → y
eq(0', 0') → true
eq(0', s(x)) → false
eq(s(x), 0') → false
eq(s(x), s(y)) → eq(x, y)
app(nil, l) → l
app(cons(x, l1), l2) → cons(x, app(l1, l2))
app(app(l1, l2), l3) → app(l1, app(l2, l3))
mem(x, nil) → false
mem(x, cons(y, l)) → ifmem(eq(x, y), x, l)
ifmem(true, x, l) → true
ifmem(false, x, l) → mem(x, l)
inter(x, nil) → nil
inter(nil, x) → nil
inter(app(l1, l2), l3) → app(inter(l1, l3), inter(l2, l3))
inter(l1, app(l2, l3)) → app(inter(l1, l2), inter(l1, l3))
inter(cons(x, l1), l2) → ifinter(mem(x, l2), x, l1, l2)
inter(l1, cons(x, l2)) → ifinter(mem(x, l1), x, l2, l1)
ifinter(true, x, l1, l2) → cons(x, inter(l1, l2))
ifinter(false, x, l1, l2) → inter(l1, l2)

Types:
if :: true:false → if → if → if
true :: true:false
false :: true:false
eq :: 0':s → 0':s → true:false
0' :: 0':s
s :: 0':s → 0':s
app :: nil:cons → nil:cons → nil:cons
nil :: nil:cons
cons :: 0':s → nil:cons → nil:cons
mem :: 0':s → nil:cons → true:false
ifmem :: true:false → 0':s → nil:cons → true:false
inter :: nil:cons → nil:cons → nil:cons
ifinter :: true:false → 0':s → nil:cons → nil:cons → nil:cons
hole_if1_0 :: if
hole_true:false2_0 :: true:false
hole_0':s3_0 :: 0':s
hole_nil:cons4_0 :: nil:cons
gen_0':s5_0 :: Nat → 0':s
gen_nil:cons6_0 :: Nat → nil:cons

Lemmas:
eq(gen_0':s5_0(n8_0), gen_0':s5_0(n8_0)) → true, rt ∈ Ω(1 + n80)
app(gen_nil:cons6_0(n583_0), gen_nil:cons6_0(b)) → gen_nil:cons6_0(+(n583_0, b)), rt ∈ Ω(1 + n5830)

Generator Equations:
gen_0':s5_0(0) ⇔ 0'
gen_0':s5_0(+(x, 1)) ⇔ s(gen_0':s5_0(x))
gen_nil:cons6_0(0) ⇔ nil
gen_nil:cons6_0(+(x, 1)) ⇔ cons(0', gen_nil:cons6_0(x))

No more defined symbols left to analyse.

### (22) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
eq(gen_0':s5_0(n8_0), gen_0':s5_0(n8_0)) → true, rt ∈ Ω(1 + n80)

### (24) Obligation:

TRS:
Rules:
if(true, x, y) → x
if(false, x, y) → y
eq(0', 0') → true
eq(0', s(x)) → false
eq(s(x), 0') → false
eq(s(x), s(y)) → eq(x, y)
app(nil, l) → l
app(cons(x, l1), l2) → cons(x, app(l1, l2))
app(app(l1, l2), l3) → app(l1, app(l2, l3))
mem(x, nil) → false
mem(x, cons(y, l)) → ifmem(eq(x, y), x, l)
ifmem(true, x, l) → true
ifmem(false, x, l) → mem(x, l)
inter(x, nil) → nil
inter(nil, x) → nil
inter(app(l1, l2), l3) → app(inter(l1, l3), inter(l2, l3))
inter(l1, app(l2, l3)) → app(inter(l1, l2), inter(l1, l3))
inter(cons(x, l1), l2) → ifinter(mem(x, l2), x, l1, l2)
inter(l1, cons(x, l2)) → ifinter(mem(x, l1), x, l2, l1)
ifinter(true, x, l1, l2) → cons(x, inter(l1, l2))
ifinter(false, x, l1, l2) → inter(l1, l2)

Types:
if :: true:false → if → if → if
true :: true:false
false :: true:false
eq :: 0':s → 0':s → true:false
0' :: 0':s
s :: 0':s → 0':s
app :: nil:cons → nil:cons → nil:cons
nil :: nil:cons
cons :: 0':s → nil:cons → nil:cons
mem :: 0':s → nil:cons → true:false
ifmem :: true:false → 0':s → nil:cons → true:false
inter :: nil:cons → nil:cons → nil:cons
ifinter :: true:false → 0':s → nil:cons → nil:cons → nil:cons
hole_if1_0 :: if
hole_true:false2_0 :: true:false
hole_0':s3_0 :: 0':s
hole_nil:cons4_0 :: nil:cons
gen_0':s5_0 :: Nat → 0':s
gen_nil:cons6_0 :: Nat → nil:cons

Lemmas:
eq(gen_0':s5_0(n8_0), gen_0':s5_0(n8_0)) → true, rt ∈ Ω(1 + n80)

Generator Equations:
gen_0':s5_0(0) ⇔ 0'
gen_0':s5_0(+(x, 1)) ⇔ s(gen_0':s5_0(x))
gen_nil:cons6_0(0) ⇔ nil
gen_nil:cons6_0(+(x, 1)) ⇔ cons(0', gen_nil:cons6_0(x))

No more defined symbols left to analyse.

### (25) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
eq(gen_0':s5_0(n8_0), gen_0':s5_0(n8_0)) → true, rt ∈ Ω(1 + n80)